2013
DOI: 10.1007/s00204-013-1123-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary hepatocytes and their cultures in liver apoptosis research

Abstract: Apoptosis not only plays a key role in physiological demise of defunct hepatocytes, but is also associated with a plethora of acute and chronic liver diseases as well as with hepatotoxicity. The Europe PMC Funders Group Europe PMC Funders Author ManuscriptsEurope PMC Funders Author Manuscripts present paper focuses on the modelling of this mode of programmed cell death in primary hepatocyte cultures. Particular attention is paid to the activation of spontaneous apoptosis during the isolation of hepatocytes f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 141 publications
(212 reference statements)
0
20
0
1
Order By: Relevance
“…For the first time to our knowledge, we describe that IFN-γ signal transduction in hepatocytes, via activation of STAT1 and transactivation of the Mlkl promoter, rapidly increased the amount of MLKL transcripts and protein, which are low under steady-state conditions. PMHs display spontaneous cell death during long-term cell culture but show rather low sensitivity to necroptosis induction by TNF-α/zVAD/SMAC mimetic treatment (43,48). However, pretreatment of mice or cells with IFN-γ upregulated Mlkl in hepatocytes and increased their susceptibility toward cell death (Supplemental Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…For the first time to our knowledge, we describe that IFN-γ signal transduction in hepatocytes, via activation of STAT1 and transactivation of the Mlkl promoter, rapidly increased the amount of MLKL transcripts and protein, which are low under steady-state conditions. PMHs display spontaneous cell death during long-term cell culture but show rather low sensitivity to necroptosis induction by TNF-α/zVAD/SMAC mimetic treatment (43,48). However, pretreatment of mice or cells with IFN-γ upregulated Mlkl in hepatocytes and increased their susceptibility toward cell death (Supplemental Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…The main obstacle is a confined hepatocyte proliferation and expansion rate in the 2D system. For instance, the hepatocyte proliferation rate is commonly decreased 3 to 5 days post-isolation and these cells are prone to de-differentiate and acquire fibroblast-like phenotype by modulation of hepatic-associated genes, leading to cell functionality removal and limitation of activity [148,149]. It has shown that the secretion of Alb, synthesis of urea, and expression of gene CYP3A4 are decreased in freshly isolated hepatocytes [150,151].…”
Section: D Printing Role On Cell Fate Toward a Hepatic-like Phenotypementioning
confidence: 99%
“…Upon dedifferentiation, hepatocytes adopt a fibroblast-like flattened phenotype. Hepatocytes either swell and become leaky, or shrink and produce apoptotic bodies when dying by necrosis or apoptosis, respectively (Fraczek et al 2013;Vinken et al 2014).…”
Section: Morphologymentioning
confidence: 99%